Empowering enterprise cloud transformation with AWS : address the real-world challenges and optimize outputs from cloud migration and modernization on AWS /: address the real-world challenges and optimize outputs from cloud migration and modernization on AWS. (2023) - Grandhi, Mridula
No abstract available